Drawing and Measuring to Define a Reason between Thought and Project (diségno, 2020)
Treating the genetic relationship between Drawing and measurement, without wanting to commit the references, albeit rich in meaning, that bring us back to Phidias and Polycletus and their preference for mathematical rules and geometric order as the necessary basis for any artistic expression, or to the Plato himself and his obvious impossibility of separating the doctrine of numbers, measure and balance from the arts, up to the conception of Saint Augustine which takes up the maximum Solomonic “Ordo, pondo et mensura” in his conception of God, origin of the beauty that contains in itself number, measure and harmony [cf. Ungers 1994, pp. 307-318], and to all the developments that have originated from these assumptions inherent in harmonic-proportional theories, it means investigating a subtle condition of balance, a horizon that moves towards the territories of knowledge and explains the principles that aim to permute the design in the dimension of the restitutive and planning double prefiguration (read more).